STUDENTS’ PROBLEMS ON BLENDED LEARNING PRACTICE: A CASE STUDY AT ELEMENTARY SCHOOL IN A NEW NORMAL OF COVID-19 - Lalu Zulpadli; Rahimah Embong (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
Up to now, no one can predict when the COVID-19 outbreak will end. Education as one of the affected sectors is necessary to adjust to existing conditions in what we call a new normal. The learning process in the new normal is much different from previous learning because it should follow any stipulation including school should obey health protocols, the number of students is not more than half the capacity of the classroom, the face-to-face learning in class is reduced to half of the available time. Blended learning is chosen as a learning strategy to be applied in elementary school. The sudden application of blended learning strategy in elementary schools raises many problems, including those faced by students. Hence, this study investigates the problems faced by students at elementary school. This study used a qualitative approach with a case study design. To collect data, this study used data collection techniques in the form of interviews, observations, and documentation. Data are analyzed using the concept of Miles and Huberman, started by reductions, data display, and verifications or conclusions. The result of this study shows some aspects of the problem faced by students consist of 1) Infrastructure and connectivity, 2) technological competency, 3) self-regulation and isolation, and 4) learning environment problems.